2007
DOI: 10.1016/j.jasms.2007.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Application of laser induced electron impact ionization to the deposition chemistry in the hot-wire chemical vapor deposition process with SiH4-NH3 gas mixtures

Abstract: The application of a laser-induced electron impact (LIEI) ionization source in studying the gas-phase chemistry of the SiH(4)/NH(3) hot-wire chemical vapor deposition (HWCVD) system has been investigated. The LIEI source is achieved by directing an unfocused laser beam containing both 118 nm (10.5 eV) vacuum ultraviolet (VUV) and 355 nm UV radiations to the repeller plate in a time-of-flight mass spectrometer. Comparison of the LIEI source with the conventional 118 nm VUV single-photon ionization (SPI) method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…These results are consistent with the proposed formation mechanism, whereby production of NH 2 radicals from NH 3 decomposition acts as the limiting factor in aminosilane formation. As shown in our previous work regarding the interplay of the NH 3 and SiH 4 components in the gas-phase reaction chemistry in HWCVD, by raising the amount of NH 3 in the mixtures, the decomposition efficiency of NH 3 increases 14 . This, in turn, results in the production of more NH 2 radicals and consequently more tetraaminosilane will form.…”
Section: 23supporting
confidence: 51%
See 3 more Smart Citations
“…These results are consistent with the proposed formation mechanism, whereby production of NH 2 radicals from NH 3 decomposition acts as the limiting factor in aminosilane formation. As shown in our previous work regarding the interplay of the NH 3 and SiH 4 components in the gas-phase reaction chemistry in HWCVD, by raising the amount of NH 3 in the mixtures, the decomposition efficiency of NH 3 increases 14 . This, in turn, results in the production of more NH 2 radicals and consequently more tetraaminosilane will form.…”
Section: 23supporting
confidence: 51%
“…Recent work by Umemoto et al regarding the deposition chemistry of the NH 3 -SiH 4 mixtures in the Cat-CVD processes has shown that the silyl (SiH 3 ) and amidogen (NH 2 ) radicals are the major deposition species for silicon nitride 11 . The suppression effect of SiH 4 presence in the mixtures on the NH 3 dissociation efficiency has also been demonstrated by several groups [12][13][14] . This is consistent with the fact that a high gas flow rate ratio of NH 3 to SiH 4 is typically needed under practical deposition conditions for silicon nitride films.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Endler et al [16] reported the deposition of a-Si 3 N 4 by PECVD, using SiCl 4 -N 2 -H 2 at a substrate temperature of 900 1C. Recently, silicon nitride thin films deposited by hot-wire chemical vapor deposition (HWCVD) have attracted an interest owing to a low hydrogen content [4,8,17,18]. However, silicon nitride films deposited by HWCVD were amorphous under deposition conditions of wire temperatures of 1500-2000 1C, substrate temperatures of 200-500 1C and reactor pressures of 0.001-0.5 Torr [4,5,8,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%